Peran Keterlibatan Pegawai Dalam Pengaruh Kenyamanan Lingkungan Kerja, Komunikasi Dan Manajemen Waktu Terhadap Kinerja Pegawai Di Lingkungan Pemerintah Provinsi Kepulauan Riau - Novita, Eriza; Setyawan, Agustinus; Sudhartio, Lily (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Research aim: This finding can provide a purpose for interpreting the determination of employee involvement in the influence of work environment comfort, communication, and time management on employee performance. Methode: This finding uses primary data. Respondents were selected by an accidental sampling technique, namely by giving questionnaires in the form of Google Forms to respondents and making them accessible to researchers based on predetermined criteria. Research Finding: The findings interpret that the workplace environment may have little impact on productivity but that effective communication and time management are likely to have wide-ranging benefits for the organization. Theoretical contribution: This research contributes to the human resource management literature by showing that time management and employee engagement significantly impact employee performance. The findings strengthen existing theories and offer a new perspective by integrating both concepts within the theoretical framework. By emphasizing the role of time management as a driver of employee engagement, this study provides deeper insights into the relationship between time management, engagement, and performance and opens up opportunities for further research in this area. Practitionel implication: Organizations should implement a structured and regular performance evaluation system to provide necessary employee feedback. In addition, training on time management and effective communication should be provided to enhance employee engagement. Establishing a comfortable working environment and a culture of open communication will encourage active employee participation. Monitoring and following up on employee satisfaction and implementing a reward system for outstanding employees are also critical. Organizations can improve employee performance and create a positive work culture with these measures. Research limitation: This research has several limitations. Among them, the research focuses only on the State’s Civil Apparatus in the Riau Islands Provincial Government, so the findings may not be generalizable to other sectors or locations. Then, the use of questionnaires as a data collection method may cause respondent bias, which may affect the accuracy of the results. Furthermore, this study did not consider other external factors that may affect employee performance, such as economic conditions or applicable government policies.